Mechanisms of enhancement of light emission in nanostructures of II–VI compounds doped with manganese - Godlewski, M.; Yatsunenko, S.; Ivanov, V.Yu.; Drozdowicz-Tomsia, K.; Goldys, E.M.; Phillips, M.R.; Klar, P.J.; Heimbrodt, W. (Физика низких температур, 2007)
Intra-shell transitions of transition metal and rare earth ions are parity forbidden processes.
For Mn²⁺ ions this is also a spin forbidden process, i.e., light emission should be inefficient. Surprisingly,
it was reported that in nanostructures of ZnMnS the ⁴T₁ to ⁶A₁ intra-shell transition of
Mn²⁺ results in a bright photoluminescence characterized by a short PL decay time. The model of a
quantum confined atom was introduced to explain the observed experimental results. It was later
claimed that this model is incorrect. Based on the results of our photoluminescence, photoluminescence
kinetics, time-resolved photoluminescence, electron spin resonance and optically
detected magnetic resonance investigations we confirm photoluminescence enhancement and decrease
of photoluminescence lifetime and relate these effects to spin dependent magnetic interactions
between localized spins of Mn²⁺ ions and spins/magnetic moments of free carriers. This
mechanism is active in both bulk and in low-dimensional structures, but is significantly enhanced
in nanostructure samples.